The Growing Importance of Optimal Public Transport Planning - Piotr KISIELEWSKI (Communications of International Proceedings, 2021)
The issue of urban transport planning has recently become extremely important not only from an economic point of view, but above all for the sustainable development of multidimensional city systems that affect life of their citizens. The growing importance of the organization of public transport results, on one hand, from the dynamic development of individual urban agglomerations and the number of their inhabitants, and, on the other hand, from the trend of minimizing the costs of city service from the point of view of transport organizers and the increasing expectations of users of public transport services. The number of inhabitants and the territorial expansion of cities forces the organization of efficient public transport. Public transport is the basic transport system in large urban agglomerations, without which cities would "drown" in the congestion of individual means of transport. Good functioning of public transit affects the image of the city, satisfaction of residents and visitors, efficient functioning of the agglomeration. The functioning of public transport depends on many factors, including the condition of the transit infrastructure, the technical condition of the rolling stock and, to a large extent, the management and operational planning of transport. The transport process in cities is so complex and expensive that it requires good, professional strategic and operational planning with the use of the best possible computer-aided tools applying an mathematical optimization apparatus. The paper presents the possibilities and the benefits of using mathematical optimization at many stages of public transport planning.
Keywords: Public Transport; Planning Process; Passenger Satisfaction; Cost Minimization.